# What are the solutions of the quadratic equation 0 = 4(x - 3)^{2} - 16?

**Solution:**

Given,

The quadratic equation 0 = 4(x - 3)^{2} - 16.

Using binomial theorem, (a - b)^{2} = a^{2} - 2ab + b^{2} to expand (x - 3)^{2}.

0 = 4(x^{2} - 6x + 9 ) - 16.

Using distributive property to multiply 4 by x^{2} - 6x + 9.

0 = 4x^{2} - 24x + 36 - 16.

Subtract 16 from 36 to get 20.

0 = 4x^{2} - 24x + 20.

4x^{2} - 24x + 20 = 0.

Divide both sides by 4.

x^{2} - 6x + 5 = 0.

To solve the equation, factor and rewrite as x^{2} + ax + bx + 5

a + b = -6, ab = 1(5) = 5.

a = -5, b = -1.

Rewriting x^{2} - 6x + 5 as

(x^{2} - 5x) + (-x + 5)

Factor x in the first and -1 in the second group.

x(x - 5) - (x - 5)

Factor out common term

(x - 5)(x - 1)

By solving the above, we get

x = 5, x = 1

Therefore, x = 5, x = 1.

## What are the solutions of the quadratic equation 0 = 4(x - 3)^{2} - 16?

**Summary:**

The solutions of the quadratic equation 0 = 4(x - 3)^{2} - 16 is 5 , 1.

visual curriculum